PWE-044 Gastrointestinal symptoms in the joint hypermobility syndrome. (28th May 2012) - Fikree, A; Aktar, R; Grahame, R; Aziz, Q
Abstract : Introduction: The Joint Hypermobility Syndrome (JHS) is a hereditary connective tissue disorder, characterised by hyperflexibility of the skin and joints and musculoskeletal symptoms. A high prevalence of JHS has been found in patients presenting to GI clinics with unexplained symptoms. 1 However, the range and prevalence of gastrointestinal (GI) symptoms in JHS patients coming from rheumatology clinics has never been adequately characterised or compared to other patient groups. This was our aim. Methods: Multicentre, cross sectional study in new referrals to GI clinics between April 2010 and December 2011. Patients between the ages of 16–70 with a rheumatological diagnosis of JHS were compared to those in whom JHS had been excluded, at their first GI clinic visit. The validated Bowel Disease Questionnaire was completed for GI symptom information. Clinical examination confirmed or excluded the diagnosis of JHS, using the 1998 Brighton criteria. Patients outside the age range or with limited English were excluded. GI symptoms were considered significant if they occurred at least once a week, and were compared between the two groups, adjusting for sex and age. In view of the multiple comparisons, the significance level was set at 0.005. Results: 413 patients participated: 43 with a previous rheumatological diagnosis of JHS, and 370 in whom JHS had been excluded. There were significantly more females in the JHS group (95% vs 54%, p=0.000), and they were younger (mean age: 34.6±10.97 vs 43.3±14.2, p=0.000). Abdominal pain was present in all JHS patients and was significantly more likely to be of more than 5 years duration:(OR 4.38 CI 2.1 to 9.1). Other symptoms which were significantly different between the two groups are shown in Abstract PWE-044 table 1 . There was no significant difference in the prevalence of constipation (OR 1.1), diarrhoea (OR 0.2), heartburn (OR 1.3), retrosternal chest pain (OR 2), vomiting (OR 1.2), or dyspepsia (OR 2). Conclusion: This is the first comparative study of GI symptoms in JHS patients. They have significantly more upper GI symptoms, bloating and alternating bowel habit even when adjusting for age and sex. In view of the association between JHS and unexplained GI symptoms, it is important to consider the diagnosis of JHS in patients with intractable functional GI symptoms, to enable multidisciplinary management. Further studies are needed to determine the mechanism of symptoms in these patients. Competing interests: None declared. Reference: 1. Zarate N, Farmer AD, Grahame R, et al. Unexplained gastrointestinal symptoms and joint hypermobility: is connective tissue the missing link? Neurogastroenterol Motil 2009;22 :252–e78.